The Adoption of Artificial Intelligence in UAE Education Sector - Ahmed, Fatma (2020)
Artificial Intelligence is a very emerging trend in the field of technology and it has the potential to revolutionize and transform the way humans interact with the help of machines. The role played by Artificial Intelligence in the field of education across UAE is derived in this report through identifying the way it impacts the efficiency and effectiveness of the education sector. The research paper aims to derive the different AI based technologies that can be adopted across the education sector of UAE, retrieve the several advantages that the adoption can have and to identify the key issues observed while implementing the AI based devices across the education sector of UAE. The aim of the research is derived using literature review and surveys. With the help of reviewing highly credible sources of literature pertaining to the subject, the key domains of the AI based technologies are derived, their benefits while implementing in UAE education sector are derived and the problems or issues that are faced while implementing these devices are also retrieved. Deep learning, Learning Analytics, Computer Assisted Learning (CAL) and advanced data analytics are the key domains of AI that can be used for improving the efficiency and effectiveness of teaching and learning across the education sector of UAE. it is also derived that the use of these technologies would help in providing detailed insights to the teachers about the students and using it, the teachers can customize the method of teaching for every student. It will help in making the teaching process more effective and efficient by saving the teacher’s time in many unproductive activities. Key problem identified in the adoption of AI based technologies in the education sector of UAE is the resistance from the teachers due to the training required in it. The AI based devices and technologies need to be available and accessible easily and hence, this paves the way for the future research in this field.